2020
DOI: 10.1002/jgm.3257
|View full text |Cite
|
Sign up to set email alerts
|

miR‐587 promotes cervical cancer by repressing interferon regulatory factor 6

Abstract: Background: Interferon regulatory factor 6 (IRF6) exhibits tumor-suppressive functions in several cancer types. In the present study, the antitumor properties and related pathway mechanism of IRF6 were investigated in cervical cancer. Methods: Forty-one pairs of cervical cancer specimens and para-carcinoma tissues were collected to evaluate IRF6 expression using immunohistochemical staining and miR-587. The effects of miR-587 and IRF6 on cervical cancer cell growth were explored by MTT assays and in a HeLa tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 37 publications
(82 reference statements)
2
14
0
Order By: Relevance
“…The oncomiR property of miR-587 has been documented in the study of Zhang et al ., which demonstrated that inhibition of miR-587 could restore the 5-fluorouracil-induced cell apoptosis in colorectal cancer and even cause significant declines in drug resistance [ 11 ]. Largely in agreement with our present findings, upregulation of miR-587 has been identified in cervical cancer and specific inhibitor-induced miR-587 knockdown exerts inhibitory effects on tumor growth [ 21 ]. The rescue experiments in this study unearthed that miR-587 upregulation-induced by mimics could reverse the suppressed cell proliferation and colony formation triggered by PGM5-AS1 overexpression.…”
Section: Discussionsupporting
confidence: 93%
“…The oncomiR property of miR-587 has been documented in the study of Zhang et al ., which demonstrated that inhibition of miR-587 could restore the 5-fluorouracil-induced cell apoptosis in colorectal cancer and even cause significant declines in drug resistance [ 11 ]. Largely in agreement with our present findings, upregulation of miR-587 has been identified in cervical cancer and specific inhibitor-induced miR-587 knockdown exerts inhibitory effects on tumor growth [ 21 ]. The rescue experiments in this study unearthed that miR-587 upregulation-induced by mimics could reverse the suppressed cell proliferation and colony formation triggered by PGM5-AS1 overexpression.…”
Section: Discussionsupporting
confidence: 93%
“…For instance, IRF8 functions as a tumor suppressor in RCC, and its mediated interferon signal pathway is involved in the pathogenesis of RCC [23]; RCC patients with high IRF8 expression level have prolonged OS compared to patients with low level of IRF8 expression [24]; IRF1 plays a pivotal role in the interferon-gamma-mediated-enhancement of Fas/ CD95-mediated RCC cells apoptosis [25]. Although previous studies have indicated that IRF6 also plays important roles in multiple tumors, including gastric cancer [13], nasopharyngeal carcinoma [14], squamous cell carcinoma [15] and cervical cancer [16], the expression pattern and prognostic value of IRF6 in ccRCC are still uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that IRF6, as a member of the IRFs family, plays an important role in the occurrence and development of a variety of tumors. For example, IRF6 predicts a favorable prognosis in gastric cancer [13]; IRF6 distinctively reverses stemness phenotype in nasopharyngeal carcinoma [14]; IRF6 downregulation promotes squamous cell carcinoma (SCC) cell invasive and reintroduction of IRF6 into SCC cells inhibits cell growth [15]; miR-587 promotes cervical cancer by repressing IRF6 [16]. However, the expression pattern and clinicopathological role of IRF6 and its prognostic value in ccRCC remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…6B). As miR-525 was shown to repress glioma cells proliferation in other studies [42], we chose miR-587 for subsequent analysis, for its oncogenic role in multiple cancer types [43][44][45] except glioma. So, we rst studied the function of miR-587 in glioma cells with CCK8, apoptosis and wound healing assays.…”
Section: Decreased Rnf185 Was Caused By Increased Mir-587 Expressionmentioning
confidence: 99%